2015
DOI: 10.1007/s11135-014-0155-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of corporate social responsibility reports: the case of reporting practices in selected European Union member states

Abstract: The organization may communicate its engagement in sustainability and may presents results achieved in this field by creating and publishing corporate social responsibility (CSR) reports. Today, we can observe a growing number of companies issuing such reports as a part of their annual reports or as stand-alone CSR reports. Despite the increase in the number of such reports their quality is different. CSR reports do not always provide complete data that readers desire, which in turn intensifies the problem wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(179 citation statements)
references
References 63 publications
10
161
0
8
Order By: Relevance
“…The majority of research in sustainability reporting has focused on the private sector and it has been receiving increasing amounts of attention [18][19][20][21][22][23][24]. Only in recent years has an increased interest on this topic gained traction in the public sector [25][26][27][28].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The majority of research in sustainability reporting has focused on the private sector and it has been receiving increasing amounts of attention [18][19][20][21][22][23][24]. Only in recent years has an increased interest on this topic gained traction in the public sector [25][26][27][28].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The selection of the criteria was based on the author's previous research in this topic [12,19]. It was assumed that quality of CSR reports equals the quality of the information provided in these types of reports.…”
Section: Assessment Toolmentioning
confidence: 99%
“…It has also been reported that the disclosure of non-financial information may vary according to the LG context [27]. The European Union has…”
Section: Introductionmentioning
confidence: 99%